SCHWARZ DOMAIN DECOMPOSITION METHOD - NURHA DEWI, WAKTU SAPTU (Universiti Malaysia Sarawak (UNIMAS), 2019)
Schwarz domain decomposition methods have been invented by Hermann Amandus Schwarz in 1869. Basically, the main idea of this method is to be a parallel solver and solve the parallel computation. With the advent of the parallel computing, we are going to have a very complex data to be process within a time. Schwarz methods is the best way to illustrate how it can enhance the performance in solving the computation of parallel problem where the computational domain is decomposed into subdomains. We also indicate that the boundaryvalue problem is formulated and solved independently for each subdomain by computes the parallel computation. In addition, with parallel computing, the computational time also significantly reduced, which will be helpful to enhance the performance of the data computing. The Schwarz domain decomposition method provide efficient and robust scheme for solving large systems of linear algebraic equations. With these methods, we can reduce the amount of memory used to complete the parallel computing. Parallel computing is important since it helps to make the functionality of the domain decomposition become more resourceful in solving the computation iteratively.